Producing Peanuts Using Conservation Tillage - David L. Wright; Barry L Tillman; Pratap Devkota; Ian M Small; Jay Ferrell (EDIS)
Most crops can be successfully grown using conservation planting technology.  There has been resistance in using conservation tillage planting methods for peanut as many specialists from past years promoted deep plowing to bury plant residue that might carry various disease organisms.  This document will help guide growers who want to use conservation tillage in making that change. https://edis.ifas.ufl.edu/ag187